2019
DOI: 10.1021/acsmacrolett.9b00199
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and Processable Shape-Memory Materials Based on Solvent-Free, Catalyst-Free Polycondensation between Formaldehyde and Diamine at Room Temperature

Abstract: Compared with traditional thermosets, malleable thermosets have more applications in aerospace, biotechnology, and construction. Here we report a one-step, solvent-free, catalyst-free polycondensation method between diamine and formaldehyde to prepare a series of malleable hemiaminal dynamic covalent networks (HDCNs). The materials have excellent malleability and reprocessability by hot pressing. The Young's modulus and breaking strength of HDCNs obtained by the polycondensation of formaldehyde and 4,4-diamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 60 publications
(77 reference statements)
0
45
0
Order By: Relevance
“…Similar to the reported method by Yuan et al [ 41 ], the specimens for thermal and mechanical tests were prepared as illustrated in Figure 1 b. Since both the disulfide bond and hemiaminal group are dynamic covalent bonds [ 50 , 51 ], uniform coherent PHT bars could be obtained by pressing HDCN powders at 150 °C under 0.3 MPa for 1 h. It should be noted that the PHT specimens were prepared by a hot-press process rather than direct curing in a mold. This is because there exists a high boiling point NMP solvent in the monomer mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the reported method by Yuan et al [ 41 ], the specimens for thermal and mechanical tests were prepared as illustrated in Figure 1 b. Since both the disulfide bond and hemiaminal group are dynamic covalent bonds [ 50 , 51 ], uniform coherent PHT bars could be obtained by pressing HDCN powders at 150 °C under 0.3 MPa for 1 h. It should be noted that the PHT specimens were prepared by a hot-press process rather than direct curing in a mold. This is because there exists a high boiling point NMP solvent in the monomer mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic covalent polymers have thus been shown to demonstrate many unique properties, such as self-healing ability, recyclability, stimuli-responsiveness, shape memory behavior, degradability, etc., which will be discussed in the following sections. [51][52][53][54][55][56][57]…”
Section: Properties Of Dynamic Covalent Polymersmentioning
confidence: 99%
“…A combination of the vitrimer-like behavior and SME enables many new ways to manipulate polymers, far beyond folding/unfolding, reprocessing and heating assisted healing, which have been focused on in most of the studies reported so far [ 21 , 25 , 26 ]. In this section, in addition to these well-known applications, we explore some more possibilities in reshaping (inside/outside, microscopically/macroscopically, permanent/temporary) and manufacturing using vitrimer-like SMPs and their composites.…”
Section: Applications Of Vitrimer-like Smps and Their Compositesmentioning
confidence: 99%
“…In recent years, many new types of vitrimers have been invented via different approaches for enhanced performance and/or for some special features (such as, the novel SME or self-folding/unfolding [ 21 , 22 , 23 , 24 , 25 ], i.e., reshaping), malleability and reprocessability by hot-pressing (i.e., associated with recycling as thermo-plastics) and heat-assisted healing, etc., [ 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Current methods to characterize vitrimers are mostly based on the Arrhenius law [ 17 , 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%